C70/Pentacene Organic Heterojunction as Charge Generator to Realize Highly Efficient Charge Carrier Injection in Organic Light‐Emitting Diodes: Performance and Mechanism Analysis. Issue 14 (4th May 2016) - Guo, Qingxun; Sun, Hengda; Yang, Dezhi; Qiao, Xianfeng; Chen, Jiangshan; Ahamad, Tansir; Alshehri, Saad M.; Ma, Dongge
Abstract : Highly efficient charge carrier injection from electrodes is basically required for high‐performance organic light‐emitting diodes (OLEDs). However, the mismatch of metal work function and energy level of charge carrier transport layers inevitably introduces the injection barrier and also greatly restricts the choice of the electrode metals. Here, a planar organic heterojunction (OHJ) C70 /pentacene is used as charge generator to realize the highly efficient injection of charge carriers in OLEDs, not only achieving the high efficiency but also significantly improving the stability. More importantly, the resulting devices show an electrode work function‐independent efficiency property, greatly broadening the selectivity of electrode metals. Detailed studies are presented on the transport properties of electrons and holes in single‐carrier devices based on C70 /pentacene OHJ by current density–voltage ( J–V ) measurements at various temperatures. It can be seen that Fowler–Nordheim (F–N) tunnel model can be used to well demonstrate the J–V properties, indicating that the charge injection based on OHJ is a tunnel process. The impedance measurements found that the lower lowest unoccupied molecular orbit energy level and higher electron mobility properties are very necessary for the used electron‐transport materials to reduce the space charge region width, thus realizing highly efficient electron injection. Abstract : C70 /pentacene organic heterojunction (OHJ) is employed as the new way of charge injection for high‐performance organic light‐emitting diodes, where both high injection efficiency and electrode work function‐independent property are realized. Charge injection mechanism of holes and electrons with OHJ as the new injection layer is fully analyzed.